ANALISIS STRATEGI PEMASARAN DAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN KOTA MEDAN - Veri; Hommy Dorthy Ellyany Sinaga (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the influence of marketing strategies and service quality on consumer purchasing decisions in Medan City. The rapid growth of culinary and retail MSMEs in Medan has intensified competition, requiring entrepreneurs to focus not only on product quality but also on marketing strategies and service excellence. Marketing strategies include pricing, promotion, and distribution, while service quality emphasizes responsiveness, reliability, and empathy. Using a descriptive qualitative method, data were collected through observation, interviews, and literature review. Findings reveal that effective marketing strategies attract consumers by offering value and differentiation, while service quality strengthens consumer trust and satisfaction. The synergy of both factors significantly influences purchasing decisions, where marketing strategies stimulate initial interest and service quality ensures repeat purchases. In conclusion, MSMEs in Medan must integrate creative marketing strategies with consistent service quality to enhance consumer purchasing decisions.